Security from Denial of Sleep Attack in Wireless Sensor Network - Kaur, Simerpreet; Ataullah, Md.; Garg, Monika (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
With the advancement in Wireless Sensor Network (WSN) sensors are gaining importance in the physical world. Besides the low power of sensor nodes used, sensors are widely used in detecting temperature, pollution, pressure and other various applications. Energy-constrained sensor networks periodically place nodes to sleep in order to extend the network Lifetime. Denial of sleep attacks are a great threat to lifetime of sensor networks as it prevents the nodes from going into sleep mode. In this paper we are describing prevention against Denials of sleep attack. We have analyzed each of proposed solutions, identify their strengths and limitations.